Oxygen Reduction Reaction (ORR) of Pt/C Standard in Different Electrolyte Solutions and Terbium(III) Monoporphyrinato Complex - Atmanto Heru Wibowo; Annisa Nur Buana Wati; Anas Santria; Abu Masykur; Maulidan Firdaus (Indonesian Journal of Chemistry, 2023)
Electrocatalytic parameters of a Pt/C standard and a sample of terbium(III) monoporphyrinato were investigated in different solutions. N electron transfer, Tafel slope, Eonset, and overpotential of the catalyst of Pt/C in different solutions were calculated and analyzed using a rotating ring disk electrode (RRDE) in 0.5 M H2SO4, 0.1 M HClO4 and 0.1 M NaOH. In the RRDE measurements, a bipotentiostat at a potential range of 1.03 to 0.05 V vs RHE (Ering = 1.2 V vs RHE) with a scan rate of 5 mV/s and rotation rates of 200, 400, 900, 1600 and 2500 rpm was used. Hereafter, the test of terbium(III) monoporphyrinato compound formulated in [Tb(TPP)(cyclen)]Cl (TPP = 5,10,15,20-tetraphenylporphyrinato; cyclen = 1,4,7,10-tetraazacyclododecane) as a candidate material for ORR electrocatalyst was also done. The results showed that the measurement of Pt/C standards was satisfactory according to the literature for all parameters with the n electron transfer close to 4 in all electrolytes media. [Tb(TPP)(cyclen)]Cl had an n electron transfer value of 2.38, suggesting that the [Tb(TPP)(cyclen)]Cl compound has less potential for ORR catalysts.